Menanamkan Nilai Kejujuran Anak Usia Dini melalui Metode Bercerita Berbantuan Boneka Tangan pada Kelompok B RA Al-Falah Ciroyom Bojonggambir Tasikmalaya - Novita Sari; Rina Sayidah Sopiah (Institut Madani Nusantara, 2024)
This study was motivated by the low level of honesty demonstrated by children in Group B at RA Al-Falah Ciroyom, Bojonggambir, Tasikmalaya. Preliminary observations revealed that out of 15 children, only five were willing to admit their mistakes, four remained silent when questioned, and six provided answers that did not reflect the truth. The study aimed to determine the effectiveness of a storytelling method using hand puppets in instilling the value of honesty in early childhood. A Classroom Action Research (CAR) design was employed, conducted over two cycles, with each cycle comprising five actions. Research instruments included observation sheets, teacher performance assessment sheets (APKG), journals, and documentation, while data analysis was performed using both qualitative and quantitative methods. The results indicated that the application of the hand-puppet storytelling method significantly improved the children's honesty across both cycles. The average developmental achievement score rose from 3.50 in Cycle I to 4.01 in Cycle II, reaching the